2017
DOI: 10.1017/aae.2016.47
|View full text |Cite
|
Sign up to set email alerts
|

Are Consumer Health Concerns Influencing Direct-From-Producer Purchasing Decisions?

Abstract: Abstract.Research has shown health concerns may motivate consumers to purchase foods sold at direct market outlets, yet connections between management of specific diseases and food purchase decisions remain unclear. We utilize a two-step decision framework to evaluate whether family incidences of six illnesses (cancer, heart disease, diabetes, obesity, back/joint pain, and Alzheimer's disease/dementia) affect decisions to buy food at farmers' markets and farm stands. We find that cancer, diabetes, obesity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…The finding from our study that DMCs are more likely than the rest of the population to be affected by obesity or chronic diet-related diseases could explain why they tend to frequent these markets, that offer more fresh produce. This corroborates results of a study on personal illness and the use of farmers' markets or on-farm kiosks, which found various positive associations between the two, that depended on the type of market, the type of illness, and whether the person affected was the one making the purchases or others in their family [59].…”
Section: Discussionsupporting
confidence: 88%
“…The finding from our study that DMCs are more likely than the rest of the population to be affected by obesity or chronic diet-related diseases could explain why they tend to frequent these markets, that offer more fresh produce. This corroborates results of a study on personal illness and the use of farmers' markets or on-farm kiosks, which found various positive associations between the two, that depended on the type of market, the type of illness, and whether the person affected was the one making the purchases or others in their family [59].…”
Section: Discussionsupporting
confidence: 88%